The Implementation of "Independent Curriculum" at Tenth Grade of SMK Terpadu Takwa Belitang - Fiska Marina; Sodikin, Ahmad; Zulaikah, Zulaikah; Andriani, Dwi (ENJEL: English Journal of Education and Literature, 2025)
Abstract This study aims to evaluate the implementation of the Independent Curriculum across various subjects in SMK Terpadu Takwa Belitang, with a focus on the alignment of teaching modules with specified phases. Utilizing a qualitative descriptive method, the research captures real-world data through observations and descriptive analyses. The findings indicate that the Independent Curriculum has been effectively implemented at tenth grade English subjects, incorporating differentiated learning and the use of digital resources. Teachers adapt teaching materials based on student data, facilitate student potential development, and actively communicate with parents. Evaluation methods include formative assessments and reinforcement for material mastery. Challenges faced include teacher preparedness and student engagement, addressed through preparatory measures and creating a conducive learning environment.